Humoral and cell-mediated immune responses to COVID-19 vaccines up to 6 months post three-dose primary series in adults with inborn errors of immunity and their breakthrough infections - Unninayar, Dana; Falcone, Emilia L.; Chapdelaine, Hugo; Vinh, Donald C.; Top, Karina A.; Derfalvi, Beata; Issekutz, Thomas B.; Decaluwe, Hélène; Pham-Huy, Anne; Upton, Julia; Betschel, Stephen D.; Rubin, Tamar; et al. (Frontiers in Immunology, 2025)
PurposeMany individuals with inborn errors of immunity (IEIs) have poor humoral immune (HI) vaccine responses. Only a few studies have examined specific cell-mediated immune (CMI) responses to coronavirus disease 2019 (COVID-19) vaccines in this population. Therefore, the purpose of this study was to examine HI and CMI responses up to 6 months post-COVID-19 vaccine dose 3 in adults with IEIs.MethodsA multi-center prospective observational study was conducted across Canada to collect severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2)-specific HI and CMI data at 4- and 24-week intervals after vaccine doses 2 and 3 (D2 + 4wk/D2 + 24wk/D3 + 4wk/D3 + 24wk).ResultsA total of 149 adults with IEIs and 423 healthy controls were recruited from July 2021 to October 2023. Geometric mean anti-spike IgG (binding antibody units/mL) and spike-specific T-cell responses [IFN-γ+ T cells/106 peripheral blood mononuclear cells (PBMCs)] were significantly lower in IEIs compared to controls at D2 + 4wk, D3 + 4wk, and D3 + 24wk. However, at 6 months after completing the primary series (three doses for IEIs and two doses for healthy), both HI and CMI responses of both IEI participants and healthy controls persisted and were comparable. There was a strong correlation between neutralizing antibody titer (ID50) and anti-spike IgG but not between ID50 and CMI. There was only one reported case of hospitalized COVID-19 disease before and none after completing the primary series among IEI participants.ConclusionAdults with IEIs mounted both HI and CMI responses following COVID-19 vaccines, which were lower than those of healthy individuals but were present at least up to 6 months after dose 3. These data support the initial recommendation for a three-dose primary series among IEIs.